The effect of individualised sprint training in elite female team sport athletes: A pilot study - Rakovic, E.; Paulsen, G.; Helland, C.; Eriksrud, O.; Haugen, T. (Journal of Sports Sciences, 2018)
This study aimed to evaluate whether an individualised sprint-training program was more effective in improving sprint performance in elite team-sport players compared to a generalised sprint-training program. Seventeen elite female handball players (23 ± 3 y, 177 ± 7 cm, 73 ± 6 kg) performed two weekly sprint training sessions over eight weeks in addition to their regular handball practice. An individualised training group (ITG, n = 9) performed a targeted sprint-training program based on their horizontal force-velocity profile from the pre-training test. Within ITG, players displaying the lowest, highest and mid-level force-velocity slope values relative to body mass were assigned to a resisted, an assisted or a mixed sprint-training program (resisted sprinting in the first half and assisted sprinting in the second half of the intervention period), respectively. A control group (CG, n = 8) performed a generalised sprint-training program. Both groups improved 30-m sprint performance by ~1% (small effect) and maximal velocity sprinting by ~2% (moderate effect). Trivial or small effect magnitudes were observed for mechanical outputs related to horizontal force- or power production. All between-group differences were trivial. In conclusion, individualised sprint-training was no more effective in improving sprint performance than a generalised sprint-training program.